2009
DOI: 10.1590/s0104-11692009000300003
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between nurses' leadership styles and power bases

Abstract: RELACIÓN ENTRE ESTILOS DE LIDERAZGO Y BASES DE PODER EN LAS ENFERMERAS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…This could be supported by Polat and Sönmez (2018), who found that nurses perceived legitimate, expert, and referent power as reinforcing power sources and the most common power type used by their nurse managers, whereas coercive power was the least used. The obtained results are also similar to García García and Santa‐Bárbara (2009).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…This could be supported by Polat and Sönmez (2018), who found that nurses perceived legitimate, expert, and referent power as reinforcing power sources and the most common power type used by their nurse managers, whereas coercive power was the least used. The obtained results are also similar to García García and Santa‐Bárbara (2009).…”
Section: Discussionsupporting
confidence: 90%
“…Once a manager gains control of power resources valued by others, they must consider how to use them best (García García & Santa‐Bárbara, 2009). Influence tactic refers to the type of influence behaviors the managers use with their subordinates (Yukl et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Leadership is the skill and extraordinary ability to infl uence people (2) . A concept of leadership, known as the Great Man Theory, evolved into the study of the leadership traits of great leaders who dealt with situational issues and issues of productivity, quality and job satisfaction (3) with competence and emotional intelligence (4) .…”
Section: Introductionmentioning
confidence: 99%